Formulating LandGem model for estimation of landfill gas under Indian scenario. (1st January 2014) - Sil, Avick; Kumar, Sunil; Kumar, Rakesh
Mostly in India, solid waste without any segregation is deposited into open dumping sites. Through these sites, there is uncontrolled emission of methane and landfill gas. The landfill gas has tremendous potential in terms of converting and using them as source of fuel. The emission of landfill gas depends on types of wastes, its rate of biodegradability, its methane potential, level of segregation and many more. In order to estimate the level of landfill gas emission, there are various US EPA recommended models are available. One of them is LandGem. But this model has been derived as per the US climatic conditions and their type of waste. It is needed to be converted into Indian conditions before applying it for Indian landfill site. This paper formulates the criteria required for converting the LandGem equation as per Indian condition and using it for Indian landfill sites. The model is verified with its application for two landfills sites of Mumbai, Deonar and Mulund.